MEDICAL-SOCIAL ASPECTS OF CHILD DISABILITY - Kasimova, Dilfuza A. (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the study was to examine the age characteristics of childhood disability, identifying risk factors contributing to its formation.Materials and methods. The prevalence of childhood disability in Tashkent studied a continuous method in dynamics over the period 2010-2018. Investigation of causes of disability, circumstances and lifestyles of children with disabilities and their families conducted in 2016-2018.Results. The study found that among children with disabilities make up 31,3% of preschool children, 51,3% of school-age children. Disabled children aged 15-16 years was 17,4%. Consequently, 82,6% of children disability has been established in pre-primary, secondary and primary school age. Among boys with disabilities was higher (54,8%) than girls.Conclusion. Child disability in Tashkent have specific age-sex characteristics: one third of disability is established in the preschool years. With increasing age of child birth causes of childhood disability significantly reduced, and acquired increased: in all age groups takes place to identify children with congenital disorders.